INFLUENCE OF MICRODOSE OF FATTY ACIDS OF CITRULLUS COLOCYNTHIS EXTRACT ON LIPOPROTEIDS OF RAT BLOOD WITH DIABETES MELLITUS TYPE 1 - Kryvosheyeva, Oksana; Garkava, Katerina; Natrus, Larysa (Proceedings of National Aviation University, 2017)
Purpose: To investigate the effect of microdoses of fatty acids (FA) of partially defatted dry Citrullus colocynthis extract on the lipid metabolism of rats with type 1 diabetes mellitus (DM) has been studied. Methods: Raw materials were degreased by extraction in a Soxhlet apparatus under conditions of shortening the evaporation time. With the help of gas-liquid chromatographic research, trace concentrations of FA were revealed in the composition of the obtained dry extract of Citrullus colocynthis. Results: It was found that the introduction of the extract of the Citrullus colocynthis vegetal solution with a dose of 400 mg/kg to rats causes redistribution of the classes of lipoproteins to the values of the control group. The dose of 200 mg/kg – does not cause statistically significant changes in plasma lipoproteins. Conclusions: Finally the Citrullus colocynthis extract containing micro doses of FA in their uniform distribution has a positive effect on lipid metabolism, does not bring to an increase of level of the total cholesterol, does not cause an increase of body weight.